2017
DOI: 10.1371/journal.pone.0174959
|View full text |Cite
|
Sign up to set email alerts
|

Driver behavior profiling: An investigation with different smartphone sensors and machine learning

Abstract: Driver behavior impacts traffic safety, fuel/energy consumption and gas emissions. Driver behavior profiling tries to understand and positively impact driver behavior. Usually driver behavior profiling tasks involve automated collection of driving data and application of computer models to generate a classification that characterizes the driver aggressiveness profile. Different sensors and classification methods have been employed in this task, however, low-cost solutions and high performance are still researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(118 citation statements)
references
References 29 publications
0
118
0
Order By: Relevance
“…Multi-day driving simulator research has shown how to calculate errors scores (based on, e.g., recorded lane keeping inaccuracies) and violations scores per driver [39] (e.g., based on speed, headway, and red light violations [40]). Various on-road studies have shown that it is possible to create a driver risk profile using sensors in smartphones (e.g., accelerometers, GPS) and vehicle sensors (e.g., [41][42][43][44]).…”
Section: Who Makes Errors and Violations?mentioning
confidence: 99%
“…Multi-day driving simulator research has shown how to calculate errors scores (based on, e.g., recorded lane keeping inaccuracies) and violations scores per driver [39] (e.g., based on speed, headway, and red light violations [40]). Various on-road studies have shown that it is possible to create a driver risk profile using sensors in smartphones (e.g., accelerometers, GPS) and vehicle sensors (e.g., [41][42][43][44]).…”
Section: Who Makes Errors and Violations?mentioning
confidence: 99%
“…In different studies, these windows could partially overlap or not overlap at all (Hokkanen et al, 2011;Lush et al, 2016;le Roux et al, 2017). An application example very similar to our approach is the assessment of car driver aggressiveness using continuous data by Ferreira et al (2017). However, to our knowledge, this approach has never been used on burst data in wildlife ecology.…”
Section: Moving Windowmentioning
confidence: 97%
“…In [5] the authors proposed using different Android smartphone sensors and classification algorithms in order to profile driver behavior. Generally, user profiling is a task that includes a preliminary identification of the profiled subject.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, user profiling is a task that includes a preliminary identification of the profiled subject. Moreover, in this survey, the authors analyzed several methods based on machine learning approaches, i.e., artificial neural networks (ANN), support vector machines (SVM), random forest (RF), and Bayesian network (BN) [5]. They confirmed that the gyroscope and the accelerometer are the best sensors to detect the driving behavior (although they confirmed that as general rule, using all sensor axes perform better than using a single one), whereas in terms of…”
Section: Introductionmentioning
confidence: 99%